The fishes of the series Capriformes, Ephippiformes, and Squamipennes, collected by the United States Bureau of fisheries steamer - Fowler, Henry W.; Bean, Barton A. (Washington U.S. Govt. Printing Office, 1929)
At head of title: Contributions to the biology of the Philippine archipelago and adjacent regions.
Keywords: Fishes; Albatross (Steamer)